Secularized and Multi-Religious Classroom Practice-Discourses and Interactions - Karin Kittelmann Flensner (Education Sciences, 2018)
Secularization and diversity are two social features that characterize the contemporary world. The rhetoric of the public debate in a number of countries has become increasingly polarized and characterized by a “we” and “them” thinking that relates a national “we” to a specific religion. This occurs in part as a reaction to the changes in national monocultural paradigms as most communities today are characterized by pluralism regarding lifestyles, religion, language and geographical background. Thus, secularization processes are ongoing while many countries, not least Sweden, are becoming increasingly pluralistic and multi-religious. The school and classrooms are a mirror of the communities they are a part of. The aim of the article is to explore how secularization and increasing pluralism finds expression and interact in the classroom practice of Religious Education. The analysis is based on ethnographic data from classroom observations of Religious Education in four different Swedish upper secondary schools. The results indicate that secularism and non-religious positions are considered a neutral and objective position and that secularism is used as a way to maneuver diversity in the classroom which affects the possibilities of dialogue and understanding.